Penerapan Art Therapy Terhadap Kemampuan Pasien Mengontrol Halusinasi pada Asuhan Keperawatan Pasien dengan Halusinasi Pendengaran di Rumah Sakit Umum Madani Palu - Adrias S Toparoa (Madago Nursing Journal, 2022)
Background: Mental disorders are psychological or behavioral disorders that occur in a person, generally associated with affective, behavioral, cognitive and perceptual disorders. Schizophrenic patients have symptoms including thought process disorders, affective and emotional disorders, volitional disorders, psychomotor disorders and secondary symptoms in the form of delusions and hallucinations. Hallucinations are one of the symptoms of mental disorders where the client experiences changes in sensory perception, feels false sensations in the form of sound, sight, taste, touch or smell. The client feels a stimulus that is not actually there. Schizophrenia is a major disorder in thought processes and disharmony between thought processes, affect and emotions. Schizophrenia has the main symptom of decreased sensory perception, namely hallucinations. Destination : To apply Art Therapy to the Nursing Care of Patients with Auditory Hallucinations at Madani Hospital Palu. Research methods : Descriptive Research with Case Study approach. Measuring instrument : The measuring instrument used to relieve auditory hallucinations is using an observation sheet. Research result : It was found that the patient's complaint during the assessment was that the patient looked restless, often paced back and forth the patient said he heard whispering sounds like he wanted to scold people, the patient said the voice came when the patient was alone and before going to sleep. with nursing diagnoses Auditory hallucinations. The nursing intervention carried out a strategy for implementing auditory hallucinations, namely training how to rebuke, converse, doing activities, one of which was Art Therapy, taking medication regularly. Suggestion :Conclusion: The application of Art Therapy can control hallucinations at Madani Hospital Palu. Suggestion : It is hoped that nurses can apply Art Therapy to patients who experience hallucinations.